Effects of a Cognitively Challenging Agility Boot Camp Program on Balance and Gait in People With Parkinson's Disease: Does Freezing of Gait Status Matter?. (September 2022) - Shah, Vrutangkumar V.; Vitorio, Rodrigo; Hasegawa, Naoya; Carlson-Kuhta, Patricia; Nutt, John G.; King, Laurie A.; Mancini, Martina; Horak, Fay B.
Background and Aim: Individuals with Parkinson's disease (PD) with and without freezing of Gait (FoG) may respond differently to exercise interventions for several reasons, including disease duration. This study aimed to determine whether both people with and without FoG benefit from the Agility Boot Camp with Cognitive Challenges (ABC-C) program. Methods: This secondary analysis of our ABC-C trial included 86 PD subjects: 44 without FoG (PD−FoG) and 42 with FoG (PD + FoG). We collected measures of standing sway balance, anticipatory postural adjustments, postural responses, and a 2-minute walk with and without a cognitive task. Two-way repeated analysis of variance, with disease duration as covariate, was used to investigate the effects of ABC-C program. Effect sizes were calculated using standardized response mean (SRM) for PD−FoG and PD + FoG, separately. Results: The ABC-C program was effective in improving gait performance in both PD−FoG and PD + FoG, even after controlling for disease duration. Specifically, dual-task gait speed ( P < .0001), dual-cost stride length ( P = .012), and these single-task measures: arm range of motion ( P < .0001), toe-off angle ( P = .005), gait cycle duration variability ( P = .019), trunk coronal range of motion ( P = .042), and stance time ( P = .046) improved in both PD−FoG and PD + FoG. There was no interaction effect between time (before and after exercise) and group (PD−FoG/PD + FoG) in all 24 objective measures of balance and gait. Dual-task gait speed improved the most in PD + FoG (SRM = 1.01), whereas single-task arm range of motion improved the most in PD−FoG (SRM = 1.01). Conclusion: The ABC-C program was similarly effective in improving gait (and not balance) performance in both PD−FoG and PD + FoG.